s-Triazine: A Privileged Structure for Drug Discovery and Bioconjugation - Sharma, Anamika (Molecules, 2021)
This review provides an overview of the broad applicability of s-triazine. Our many years working with this intriguing moiety allow us to discuss its wide activity spectrum (inhibition against MAO-A and -B, anticancer/antiproliferative and antimicrobial activity, antibacterial activity against MDR clinical isolates, antileishmanial agent, and use as drug nano delivery system). Most of the compounds addressed in our studies and those performed by other groups contain only N-substitution. Exploiting the concept of orthogonal chemoselectivity, first described by our group, we have successfully incorporated different nucleophiles in different orders into s-triazine core for application in peptides/proteins at a temperature compatible with biological systems.